EX-DIVIDEND DATE DAN PERUBAHAN HARGA SAHAM - Novriyanthi Taungke; S Supramono (University of Merdeka Malang, 2015)
The aim of this study is to analyze whether the stock prices decrease at ex-dividend date in Indonesia Stock Exchange (IDX) that is determined by amount of dividend drop-off ratio (DDR). This study also attempts to investigate the differences the stock prices decrease at ex-dividend date based on Investment Opportunity Set (IOS). Sample consist of the companiesthat announced the dividend during 2010-2012 periods. By using non-parametric tests, especially Chi-square Test and Mann Whitney Test, the result of this study showed the stock prices decreased less than dividend amount on ex-dividend date. Besides, the non-growth firms experienced decrease more than growth firms.